The interaction effect of family ownership, board gender and skills on CSR strategy with ESG performance: evidence from ASEAN-5 countries - Ab Aziz, Noor Hidayah; Abdul Latiff, Ahmed Razman; Osman, Mohammad Noor Hisham; Alshdaifat, Sajead Mowafaq (Emerald Publishing, 2024)
Purpose: This study aims to examine how corporate social responsibility (CSR) strategy impacts environmental, social and governance (ESG) performance in public listed firms across the Association of Southeast Asian Nations (ASEAN)-5 countries. Additionally, it examines the interaction effect of family ownership, board gender diversity and board skills on the relationship. Design/methodology/approach: This study used a fixed-effect panel regression to analyse 1,212 observations collected from ASEAN-5 public listed firms, covering the years 2017–2022. To address the endogeneity problem, this study used a two-step GMM. Findings: The findings indicate that the ESG performance of firms in ASEAN-5 countries is significantly and positively influenced by their CSR strategy, suggesting that robust CSR strategies lead to superior ESG performance. Family ownership is found to weaken the positive impact of CSR strategy on ESG performance, indicating that family firms prioritize CSR less. Furthermore, female and skilful boards are more likely to implement effective CSR strategies, as reflected in their improved ESG performance. Practical implications: This study urges firms, particularly family-owned firms, to enhance their CSR strategy. It also recommends that policymakers integrate gender diversity and a variety of skills into corporate boards, possibly by revising regulatory frameworks and corporate governance guidelines. Originality/value: The results of this study are novel and specifically tailored for ASEAN firms. To the best of the authors’ knowledge, this study is among the first to examine the roles of board skills, gender diversity and family ownership in the relationship between CSR strategy and ESG performance in the ASEAN context. © 2024, Emerald Publishing Limited.